2014
DOI: 10.1016/j.stemcr.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

miR-133a Enhances the Protective Capacity of Cardiac Progenitors Cells after Myocardial Infarction

Abstract: SummarymiR-133a and miR-1 are known as muscle-specific microRNAs that are involved in cardiac development and pathophysiology. We have shown that both miR-1 and miR-133a are early and progressively upregulated during in vitro cardiac differentiation of adult cardiac progenitor cells (CPCs), but only miR-133a expression was enhanced under in vitro oxidative stress. miR-1 was demonstrated to favor differentiation of CPCs, whereas miR-133a overexpression protected CPCs against cell death, targeting, among others,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 59 publications
3
106
0
Order By: Relevance
“…Other microRNAs recently identified in the CPC secretome under hypoxic conditions include: miR-292, mR-210, miR-103, miR-17, miR-199a, miR-20a and miR-15b [150]; microRNA exosomes generated after twelve hours under hypoxic conditions and injected demonstrate improved fractional shortening and reduced fibrosis in an adult rat ischemia / reperfusion model [150]. Likewise, microRNA 133a improves cardiac function through reduction of fibrosis and hypertrophy as well as increasing vascularization and cardiomyocyte proliferation in a rat myocardial infarction model [151]. Despite this relatively recent flurry of excitement regarding exosome-mediated effects, the mechanistic basis remains poorly understood and the long-term benefits in terms of restoring myocardial structure and function remain to be assessed.…”
Section: Current Status Of Adult Stem Cell Therapiesmentioning
confidence: 99%
“…Other microRNAs recently identified in the CPC secretome under hypoxic conditions include: miR-292, mR-210, miR-103, miR-17, miR-199a, miR-20a and miR-15b [150]; microRNA exosomes generated after twelve hours under hypoxic conditions and injected demonstrate improved fractional shortening and reduced fibrosis in an adult rat ischemia / reperfusion model [150]. Likewise, microRNA 133a improves cardiac function through reduction of fibrosis and hypertrophy as well as increasing vascularization and cardiomyocyte proliferation in a rat myocardial infarction model [151]. Despite this relatively recent flurry of excitement regarding exosome-mediated effects, the mechanistic basis remains poorly understood and the long-term benefits in terms of restoring myocardial structure and function remain to be assessed.…”
Section: Current Status Of Adult Stem Cell Therapiesmentioning
confidence: 99%
“…Since microRNAs have been described to play a role in cardiac pathological fibrosis3536373839,cardiomyocyte proliferation, progenitors commitment and differentiation40414243, TGF-β-mediated epithelial-to-mesenchymal transition44, and to correlate with CDCs therapeutic potential4546, we selected a panel of miRNA genes to be analyzed in BB and NBB-CDCs20. Preference was given to those miRNAs showing altered expression due to β-blocking agents observed in other systems6747484950.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of miR-1 can enhance embryonic stem cells differentiation into cardiomyocytes59, and was also shown to be upregulated upon induction of cardiac differentiation of human cardiac progenitors isolated from fetal heart42. MiR-133a has been shown to exert a protective anti-apoptotic effect on cardiomyocytes exposed to oxidative stress, and transplantation of miR-133a-overexpressing CDCs promoted increased functional recovery in a murine MI model43. Moreover, cardioprotective miR-133a expression can be induced in vitro by β-blocker carvedilol treatment48.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miRNA may also become the important biological marker for the myocardial injury, which would greatly contribute to the early diagnosis and prevention of acute myocardial infarction [18,19] . Lawrie et al found the miRNA in the human serum in 2008 [20] .…”
Section: Discussionmentioning
confidence: 99%